PERAN DEWAN PENGUPAHAN DALAM PERENCANAAN UPAH MINIMUM KOTA MALANG - Dian Rohmawati (Universitas Tribhuwana Tunggadewi, 2014)
Demonstrations in May Day celebration and minimum wage establishment shows worker's dissatisfaction about the wage that received. The important of stakeholder involvement in wage planning, mainly employers and workers and supported by healthy and harmonious coordination between government, employment and worker enable for achievement of fair wage for every parties. Ethnographic approach used to obtain the answer on how the roles of board of wage in minimum wage planning and the factors that influencing to the role. The research focuses on wage’s planning stages both in the process in preparation of materials, discussion and recommendation’s submission. Local institution, board of wage can play a role as stakeholder’s communication and participation place to realize the achievement of a fair wage that is capable of representing any aspirations. It is also been able to provide an alternative in the decision by the mayor even though there are several factors inhibiting including different interest, and difference in perception between the employers and workers in the implementation of role